Informing the development of diagnostic criteria for differential diagnosis of alcohol-related cognitive impairment (ARCI) among heavy drinkers: A systematic scoping review. - Lisa Jones; Lynn Owens; Andrew Thompson; Ian Gilmore; Paul Richardson (PLoS ONE)
Background Early detection and diagnosis of alcohol-related cognitive impairment (ARCI) among heavy drinkers is crucial to facilitating appropriate referral and treatment. However, there is lack of consensus in defining diagnostic criteria for ARCI. Uncertainty in attributing a diagnosis of suspected ARCI commonly arises in clinical practice and opportunities to intervene are missed. A systematic scoping review approach was taken to (i) summarise evidence relating to screening or diagnostic criteria used in clinical studies to detect ARCI; and (ii) to determine the extent of the research available about cognitive assessment tools used in 'point-of-care' screening or assessment of patients with suspected non-Korsakoff Syndrome forms of ARCI. Methods We searched Medline, PsycINFO, Cinahl and the Web of Science, screened reference lists and carried out forward and backwards citation searching to identify clinical studies about screening, diagnosis or assessment of patients with suspected ARCI. Results In total, only 7 studies met our primary objective and reported on modifications to existing definitions or diagnostic criteria for ARCI. These studies revealed a lack of coordinated research and progress towards the development and standardisation of diagnostic criteria for ARCI. Cognitive screening tools are commonly used in practice to support a diagnosis of ARCI, and as a secondary objective we included an additional 12 studies, which covered a range of settings and patient populations relevant to screening, diagnosis or assessment in acute, secondary or community 'point-of-care' settings. Across two studies with a defined ARCI patient sample and a further four studies with an alcohol use disorder patient sample, the accuracy, validity and/or reliability of seven different cognitive assessment tools were examined. The remaining seven studies reported descriptive findings, demonstrating the lack of evidence available to draw conclusions about which tools are most appropriate for screening patients with suspected ARCI. Conclusion This review confirms the scarcity of evidence available on the screening, diagnosis or assessment of patients with suspected ARCI. The lack of evidence is an important barrier to the development of clear guidelines for diagnosing ARCI, which would ultimately improve the real-world management and treatment of patients with ARCI.